Neoplasia in Three Aye-Ayes (Daubentonia madagascariensis). (February 2018) - Rodriguez Barbon, A.; Cowen, R.; Knott, C.; Hughes, K.; Allinson, K.; Williams, C.V.; Routh, A.
Summary: Tumours diagnosed in three aged captive aye-ayes ( Daubentonia madagascariensis ), held in two different institutions, are described. A cerebral glioblastoma was diagnosed based on histological and immunohistochemical findings in one of the animals following initial presentation with bilateral mydriasis, absent pupillary reflex, head tilt and ataxia. A second animal was humanely destroyed due to impaired locomotion associated with spondylosis and a post-mortem diagnosis of cholangiocarcinoma was made based on histology with further confirmation with immunohistochemical labelling for cytokeratin 7. A third aye-aye suffering from dental disease was diagnosed with an oral squamous cell carcinoma following an excisional biopsy from a non-healing wound in the lip. Due to progression of the neoplasia the animal was humanely destroyed and post-mortem examination revealed the presence on an additional unilateral phaeochromocytoma.